Climate Change: iBroadkas Mo! Phase 2 (Mobilizing the Rural Sector for Climate Change Adaptation and Mitigation: A Pilot Radio Campaign in the Philippines) - Progress Report - Philippine Federation of Rural Broadcasters (2019)
The report documents the activities implemented under the CCAFS SEA-funded climate change radio campaign in the Philippines from July 2018 to April 2019. The report also features the campaign outputs, complementary activities, and the broadcaster’s manual.